Tree Transplanting Evaluation in Porto Alegre, Rio Grande do Sul. - Inácio, Camila Dellanhese (2007)
Transplanting has been an alternative to save trees due to occupation projects and soil use in the big cities. Through the sampling of the 150 transplanted trees in the Porto Alegre urban zone we verified that 72% of them survived. The survival of the transplanted trees was related to the following factors: the species, its origin (native or exotic), its class (monocotyledons or dicotyledons), pruning during the transplantation, the technician in charge, and, consequently, to the techniques employed by him and his team. Native monocotyledons (palm trees) survived more than the native dicotyledons and the exotic palm trees. Jerivá (Syagrus romanzoffiana (Cham.) Glassman), corticeira-do-banhado (Erythrina crista-galli L.), and butiazeiro (Butia capitata (Mart.) Becc.) were more likely to survive in transplants. Plants that were pruned resisted significantly more than the ones that were not. The time of the year in which the transplant was performed seemed to have no effect on the survival rate.